The importance of entrepreneurship education and training programs in the promotion and the success of youth entrepreneurship - Hassani, Rekaia; Khouni, Rabeh (Sciences humaines; Vol. 30 (2013): SCIENCES HUMAINES)
You cannot teach someone to become a Bill Gates, neither can you teach someone to compose like Beethoven. But you can teach someone the notes and scales, give them the tools they need to become a composer. And you can teach the tools people need to be entrepreneurs” )Howard Stevenson of Harvard University( .i e : all the identified attributes of entrepreneurs can be positively                             affected in some manner by education. The question is not « whether » but « what » and « how » ?